The effect of liquid bound by microparticles (ions) on the membrane selectivity - Poliakov, V.L. (Доповіді НАН України, 2023)
Notion “critical concentration” was introduced for membrane processes, and a formula was proposed to calculate
it. A mathematical problem of steady-state convective-diffusive mass transfer within the layer of concentration
polarization was formulated and exactly solved, taking into account the hydration of microparticles (ions). For
numerous examples, analyses were performed to estimate the effect of hydration and mass transfer parameters on
the concentration of suspended microparticles at the membrane surface and its selectivity for uniform impurity. Стосовно мембранних процесів введено поняття критичної концентрації і запропоновано формулу для її
визначення. Сформульовано і строго розв’язано математичну задачу усталеного конвективно-дифузійного масопереносу в шарі концентраційної поляризації з урахуванням гідратації мікрочастинок (іонів). На численних прикладах для однорідних домішок проаналізовано вплив параметрів гідратації і масопереносу на концентрацію завислих мікрочастинок на поверхні мембрани, її селективність.